Thermodynamic dissection of colicin interactions. - Housden, N; Kleanthous, K (2011)
Bacteriocins are selective protein antibiotics that bind and kill specific bacterial species, the best studied of which are the colicins that target Escherichia coli. Colicins tend to parasitize cell envelope systems that are important for cell viability under nutrient-limited conditions or environmental stress. In this chapter, we review how in conjunction with other biophysical methods and structural information, isothermal titration calorimetry (ITC) has been used to investigate how colicins enter E. coli cells. In particular, we summarize current understanding of the thermodynamics of outer membrane receptor binding and how this has been linked to biological function. We also summarize thermodynamic investigations using ITC that have helped elucidate the mechanisms by which colicins bind and parasitize proteins in the periplasm, forming protein-protein interactions that ultimately trigger translocation across the outer membrane. Our review focuses on the two major cytotoxic classes of colicin that have been the subject of intense investigation, pore-forming toxins, and nonspecific endonucleases (DNases). DNase colicin-producing E. coli avoid committing suicide through the production of a small antidote protein known as the immunity (Im) protein, with the Im protein only released once cell-entry is initiated. Exosite binding by Im proteins has driven an evolutionary arms race among colicin-producing bacteria whereby markedly different colicin DNase-Im protein interaction specificities have evolved without impacting on cytotoxicity. Extensive investigations have shown that homologous colicin DNase-Im protein complexes have K(d)s, for cognate and noncognate complexes, that vary by 10-orders of magnitude, essentially matching the entire spectrum of binding affinities seen for protein-protein interactions in biology. Hence, this system has proved to be a powerful model for investigating the thermodynamics of specificity in protein-protein interactions, with ITC being the principal tool. We review this literature and point to how the thermodynamic information that has been generated complements various other kinetic and structural data.